Erectile dysfunction among diabetic patients in Kota Bharu Kelantan - Hassan, Mohd Hashim; Ismail, Ab Aziz Al Safi; Isa, Suhaimi Mohd; Yunus, Nik Noor Azmi Hohd; Salleh, Rosemi (2002)
A cross sectional study was conducted among diabetic patients in Kelantan, Malaysia to determine the prevalence of erectile dysfunction (ED),characteristics of diabetic patients with ED and patient's knowledge, attitude and practice towards ED. A total of 156 patients from Diabetic Clinic, Klinik Kesihatan Bandar, Kota Bharu and Hospital Universiti Sains Malaysia (USM), Kubang Kerian were selected into the study by using the availability sampling technique. Respondent were given self-administered questionnaire. ED was determined by using the International Index Of Erectile Function (IIEF-5). Statistical Program for Social Science (SPSS) version 9.0 was used for analyzing the data. The mean age was 53.2 ± 9.18 year. Majority of patients were Type 2 diabetes (97.6%). The overall prevalence of ED was 77.8% in which the prevalence of severe ED was 36.7%. There was significant correlation between age, duration of diabetes, history of smoking and retinopathy with ED (p<0.05). There was no significant correlation between presence of concomitant diseases with ED (p>0.05). Majority of patients (86%) had poor knowledge regarding ED.On comfort discussing about ED with the health provider, 18.2 % felt very comfortable, 32.5% felt comfortable, 15.9% felt quiet comfortable, 15.1% felt between comfortable and uncomfortable, 15.9% felt uncomfortable and 2.4% felt very uncomfortable. Regarding seeking treatment, 57.1% would do so. This study showed a high prevalence of ED in diabetic patients. The main factors associated with ED were age, duration of diabetes, history of smoking and retinopathy. Patients also considered the information on nature of ED and possible treatment were scant and generally inadequate.